Development of Online Application Program for Submission and Accountability of Budget Funds at PT. Leon Testing and Consultancy Banjarbaru - Puteri Utami, Nadia; Kartika Candra, Heru; Husnul Khatimah, Aprillia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to identify problems in the process of submitting and accounting for project budget funds at PT. Leon Testing and Consultancy Banjarbaru, and to design an application program that can simplify the process. This study uses the theoretical framework of the Accounting Information System for Submission and Accountability of Budget Funds, which includes analysis of management information, related functions, procedure networks, documents, accounting records, internal control systems, and existing flowcharts. Applicable accounting standards are used in this study, with MySQL as the backend and PHP as the frontend. The results of the study indicate that the process of submitting and accounting for funds at PT. Leon Testing and Consultancy Banjarbaru is still semi-manual, using Microsoft Excel. Therefore, it is recommended that the company adopt an online-based application to improve the efficiency and effectiveness of the process